Analysis for waste collection and management of closed-loop supply chain with dual-channel forward logistics - Xu, Lang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This paper focuses on the optimal pricing and collection rate decision for a dual-channel forward supply chain, with which the manufacturer sells products via direct channel and retail channel in the forward logistics, while the recycling competition between manufacturer and retailer exists in reverse logistics with waste. Based on game theory, we characterize the profit functions of manufacturer and retailer in closed-loop supply chain with the different scenarios of reverse logistics. By comparison the different scenario, we provide some suggestion for the manufacturer’s and retailer’s pricing and collection rate policies.